1984
DOI: 10.1007/bf00327432
|View full text |Cite
|
Sign up to set email alerts
|

Repair of UV-irradiated plasmid DNA in a Saccharomyces cerevisiae rad3 mutant deficient in excision-repair of pyrimidine dimers

Abstract: The repair of UV-irradiated DNA of plasmid pBB29 was studied in an incision-defective rad3-2 strain of Saccharomyces cerevisiae and in a uvrA6 strain of Escherichia coli by the measurement of cell transformation. Plasmid pBB29 used in these experiments contained as markers the DNA of nuclear yeast gene LEU-2 and DNA of the bacterial plasmid pBR327 with resistance to Tet and Amp enabling simultaneous screening of transformant cells in both microorganisms. We found that the yeast rad3-2 mutant, deficient in inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

1985
1985
1993
1993

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 20 publications
3
1
0
Order By: Relevance
“…In another possibility, we suggest that R A D l , 2 , 3 and 4 gene functions are required for internal enzyme transport from cytoplasm to nucleus for excision repair. These results are supported by recent similar experiments about rad3 mutant (Dominski and Jachymczyk, 1984). We consider R A D 1 , 2 , 3 and 4 gene products are probably not components of UV-specific endonuclease.…”
Section: Discussionsupporting
confidence: 91%
“…In another possibility, we suggest that R A D l , 2 , 3 and 4 gene functions are required for internal enzyme transport from cytoplasm to nucleus for excision repair. These results are supported by recent similar experiments about rad3 mutant (Dominski and Jachymczyk, 1984). We consider R A D 1 , 2 , 3 and 4 gene products are probably not components of UV-specific endonuclease.…”
Section: Discussionsupporting
confidence: 91%
“…It is interesting to note here that identical results were obtained by other laboratories with radl-1 mutants and UV-incoming DNA (White and Sedgwick, 1985;Dominski and Jachymczyk, 1987). However, Ikai et al (1985) reported that the radl-2 mutant had a normal capacity to repair UVincoming DNA although the mutant was sensitive to UV.…”
Section: Host Repair Processes Remove Uv Damage In the Incoming Dnasupporting
confidence: 86%
“…the plasmid survival was different from that found in the RAD+ host. The mutants rad2-6 (Ikai et al, 1985) and rad2 (Dominski and Jachymczyk, 1987) were able to repair UV-incoming DNA as well as the parental RA D + strains. Although different plasmid DNAs, transformation procedures and other experimental conditions were used, the differences between alleles should be further investigated.…”
Section: Host Repair Processes Remove Uv Damage In the Incoming Dnamentioning
confidence: 99%
“…They noted that, relative to a wild-type strain, transforma-tion was unaffected in the rad3-2 strain and also in radl-2, rad2-6, and rad44 strains. However, as in the study by Dominski and Jachymczyk (41), in E. coli uvrA the transformation frequency was dramatically reduced relative to that of a uvrA+ strain.…”
Section: Plasmids To Monitor Nucleotide Excision Repairsupporting
confidence: 55%